REPRESENTASI HUMANISME DALAM FILM SENYAP (THE LOOK OF SILENCE) - Restu, Bima; ", Yasir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Senyap Film is a documentary film that takes the theme of the viewpoint of the families of victims of the 1965 events in North Sumatera. The main actor in this film named Adi who is the younger brother of one of the victims of the massacre at that time named Ramli. This study aims to determine how the representation of humanism is shown in the film by using Roland Barthes semiotics analysis consisting of the meaning of denotation, connotation meaning, and semiotic myth. This research method is semiotics analysis Roland Barthes. Technique Data collection used is documentation study, observation study, literature study, and search data online. The object being analyzed are scenes contained in the movie Silent (The Look of Silence) that is as many as nine scenes. The results showed that Representation of humanism through the meaning of denotation that comes in the film Silent is how the incident at 1965, an effort to disenchant for what they have made, paranoid attitude and hatred towards PKI members. The connotations that represent humanism in the film are sadism, arrogance, egocentricity, discriminative attitudes, intimidative behavior that symbolizes very unhumanist behavior among principals. While the semiotic myths contained in the scenes are the stories circulating among the people behind the conflict that occurred between groups accused as members of the PKI and non-PKI groups in carrying out their lives today.